Unlocking The Potential of Lampung Agricultural Waste: Banana Kepok Peel Silage (Musa × Paradisiaca) for Ruminant Nutrition Through an Optimization of Ensiling Time - Deviany, Deviany; Yusuf, Reggina Aulia; Raqin, Mohammad Rayhan; Ramadhan, Aditia Fajar; Nugraha, Dea Amanda; Afriliza, Tiara Fitri (Jurnal Nutrisi Ternak Tropis, 2024)
This study investigates the optimization of ensiling time for fermenting Kepok/Saba banana peel into silage for ruminant nutrition. Two ensiling durations were compared: T1 with a 7-day ensiling time and T2 with a 14-day ensiling time. The results of the experiment reveal that while T2 demonstrated certain advantages, such as enhanced aroma and texture due to extended fermentation, the physical quality of silage from T1 was comparable, and the proximate analysis indicated no significant difference in nutritional content between T1 and T2. Additionally, T1 silage exhibited a lower crude fiber content compared to T2, suggesting potentially better digestibility and nutrient availability for livestock. These findings emphasize the practicality of choosing T1 to expedite production without compromising physical quality or nutritional integrity. The study underscores the potential of Kepok/Saba banana peel waste to be processed into silage, offering a sustainable solution for utilizing Lampung’s agricultural by-products for ruminant nutrition enhancement.